Cd4 count at the time of presentation in newly diagnosed HIV patients in a tertiary care hospital in south India: implications for the programme - Kilaru, Krishna Rajesh; Punuru, Likhita; Garimella, Venkateswara Rao; Kande, Sindhu (International Journal of Research in Medical Sciences, 2019)
Background: Lower CD4 count at initiation of antiretroviral therapy (ART) can have a significant negative impact on subsequent disease progression and mortality among HIV patients. Hence, author assessed the status of the CD4 count at the time of diagnosis and factors associated with lower CD4 count among newly diagnosed HIV cases. Methods: A prospective observational study was conducted in a single integrated counseling and testing center, affiliated with a Medical College and Hospital, Andhra Pradesh. All newly diagnosed HIV cases in the setting between January to December 2017 were included. The CD4 count was assessed as per national guidelines for enumeration of CD4 2015. Results: The final analysis included 125 participants. The mean CD4 count at diagnosis was 276.51±228.37. Only 19 (15.20%) people had CD4 count >500, 47 (37.60%) had between 200-500 and 59 (47.20%) had CD4 count <200. Only 20% had appropriate knowledge of treatment. Among the study population, 43 (34.70%) had symptomatic conditions attributed to HIV infection, 44 (35.50%) participants had an AIDS-defining illness at the time of diagnosis. Only 3 (2.40%) had voluntary counseling and testing. Even though male gender, poor educational status, having more sexual partners, poor knowledge related to HIV diagnosis and treatment was associated with higher odds of low CD4 count (<200), none of the associations were statistically significant. Conclusions: The mean CD4 count was low and almost half of newly diagnosed cases had low CD4 count (<200) at the time of diagnosis. There is a strong need to intensify the efforts to fill the gaps in the screening for the early diagnosis to maximize the benefits of HAART and to stop the spread of the infection.